Towards multifunctional thermal environmental barrier coatings (TEBCs) based on rare-earth pyrosilicate solid-solution ceramics. (September 2018) - Turcer, Laura R.; Padture, Nitin P.
Abstract: The concept of thermal environmental barrier coatings (TEBCs) for SiC-based ceramic matrix composite (CMCs) hot-section components in gas-turbine engines is elucidated. Here, a single dense TEBC layer made of low thermal-conductivity rare-earth (RE) pyrosilicate solid-solutions is expected to perform multiple functions. Several binary solid-solutions are investigated, with some satisfying the following critical requirements for dense TEBCs: (i) good thermal-expansion match with CMCs, (ii) high-temperature phase stability up to 1700 °C, (iii) low thermal conductivity, and (iv) resistance to high-temperature attack by calcia-magnesia-aluminosilicate (CMAS) melts. Other considerations and future outlook pertaining to the TEBCs concept are discussed. Graphical abstract: Unlabelled Image